2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-Glucoside modulated human umbilical vein endothelial cells injury under oxidative stress - Guo, Yan; Fan, Wenxue; Cao, Shuyu; Xie, Yuefeng; Hong, Jiancong; Zhou, Huifen; Wan, Haitong; Jin, Bo (The Korean journal of physiology & pharmacology, 2020)
Endothelial cell injury is a major contributor to cardiovascular diseases. The 2,3,5,4'-Tetrahydroxystilbene-2-O-β-D-Glucoside (TSG) contributes to alleviate human umbilical vein endothelial cells (HUVECs) injury through mechanisms still know a little. This study aims to clarify the TSG effects on gene expression (mRNA and microRNA) related to oxidative stress and endoplasmic reticulum stress induced by H2O2 in HUVECs. We found that TSG significantly reduced the death rate of cells and increased intracellular superoxide dismutase activity. At qRT-PCR, experimental data showed that TSG significantly counteracted the expressions of miR-9-5p, miR-16, miR-21, miR-29b, miR-145-5p, and miR-204-5p. Besides, TSG prevented the expression of ATF6 and CHOP increasing. In contrast, TSG promoted the expression of E2F1. In conclusion, our results point to the obvious protective effect of TSG on HUVECs injury induced by H2O2, and the mechanism may through miR16/ATF6/ E2F1 signaling pathway.